Multidrug-Resistant Pseudomonas aeruginosa Pada Intensive Care Unit Di Asia Tenggara: A Systematic Review - Suarisavitra, Ida Ayu Andhira Dewi (E-Jurnal Medika Udayana, 2022)
The incidence  of M ultidrug-resistant Pseudomonas aeruginosa is increasing in various countries requires further attention to find out the right choice of antibiotics. This review will discuss more about Pseudomonas aeruginosa resistance at the Intensive Care Unit (ICU) in Southeast Asia. The research was carried out on the PubMed, ScienceDirect, and Google Scholar databases identifying journals published from 2015 to 2020 that focus on MDRPA at the ICU  in Southeast Asia. In order to obtain a relevant study, the keywords used were accompanied by eleven Southeast Asian countries. There are 7 studies that are relevant in this study. From the study, there were 5 countries that had complete data for further analysis, namely Vietnam, Indonesia, Malaysia, Philippines, and Thailand . The prevalence of VAP is 64,7% , CAUTI 20,9%, and BSI 3,8%. Antimicrobial resistance was commonly found in sulfamethoxazole-trimethoprim (95%), linezolid (73,7%), ticarcillin-clavulanate (67,8%), amoxicillin-clavulanic acid (66,7%), and ceftriaxone (52,9%). Colistin and polymyxin B have a low resitsance rate compared to other antibiotics . I t is hope d that more researchers will be researching about MDRPA in Southeast Asia in the future and increase the sample size.